2013
DOI: 10.1097/bsd.0b013e318249599f
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiologic Outcomes of TLIF Applications With or Without Pedicle Screw

Abstract: This study showed that the TLIF procedure without pedicle screw support would be sufficient in the management of preoperatively stable patients with lumbar degenerative spinal disease requiring fusion after single-level decompression. This technique is minimally invasive, requires only unilateral intervention, allows magnetic resonance imaging during the postoperative period and is associated with less costs and complications when compared with pedicle screwing. This study represents the first prospective comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…However, due to the excessive rigidity of the system, this instrumentation is also suspected to cause decreased mineral content in the fixed area and degeneration of adjacent segments (5,19,21). To reduce this rigidity, numerous clinical and biomechanical studies were performed to find the ideal construct (8,12,14,17). Favorable results were reported for lumbar fusion in combination with a unilateral instrumentation system.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the excessive rigidity of the system, this instrumentation is also suspected to cause decreased mineral content in the fixed area and degeneration of adjacent segments (5,19,21). To reduce this rigidity, numerous clinical and biomechanical studies were performed to find the ideal construct (8,12,14,17). Favorable results were reported for lumbar fusion in combination with a unilateral instrumentation system.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study done by Kotil et al, TLIF application without pedicle screw in patients with single level lumbar disc herniation without instability was found to be as effective as pedicle screw application [6]. The advantages of TLIF application were reported to be less invasiveness, avoidance of radiological artifacts, shorter hospital stay, shorter duration of operation, lower costs, avoidance of the complications of pedicle screws and sufficient fusion rates [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although discectomy has successful clinical outcome in the early period, its success rate decreases to 40-80% in the long term due to residual low back pain and recurrence disc herniation [3][4][5]. To avoid residual low back pain and recurrence of disc herniation, combination of interbody fusion with discectomy is advised [6,7]. The necessity and efficiency of utilizing fusion after simple discectomy in patients with single segment lumbar disc herniation is still controversial [3,5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 30 patients, Kotil et al reported that a TLIF procedure without pedicle screw support would be sufficient for management of select patients after singlelevel decompression. 20 In a prospective randomized trial of 80 patients comparing unilateral pedicle screw fixation with bilateral pedicle screw fixation for 1-level and 2-level TLIF, Xue et al found comparable fusion rates and clinical outcomes between the 2 groups after a mean of 25.3 months of follow-up. 38 In a prospective trial of 87 patients undergoing 1-segment or 2-segment lumbar fusion, Suk et al demonstrated that unilateral pedicle screw fixation was as effective as bilateral instrumentation in terms of outcomes, fusion rates, and complications.…”
Section: Discussionmentioning
confidence: 99%